Feasibility of Landscape Value Trade between Landowners and Citizens in Reducing the Landscape Damage Caused by Wind Power - Mäntymaa, Erkki; Kangas, Katja; Karhu, Jouni; Pouta, Eija (Now publishers, 2024)
A mechanism of payment for ecosystem services (PES) to implement landscape value trade may partly address the visual disturbance caused by wind turbines by encouraging forest owners to change their forest management practices near housing areas close to wind farms. Here, we analyze the feasibility of implementing this mechanism in the case of landscape shields reducing the visual impacts of wind power using previous results and data on citizen and forest owner preferences. We evaluate the feasibility at various spatial scales. The results demonstrate that at the county level, willingness to pay (WTP) exceeds willingness to accept (WTA) compensation. Finally, if a PES mechanism is site-specific, its feasibility depends on how the demand for and supply of the service meet at the narrowest geographical level. In our study, the probability of agreement was low at the wind farm level (2%) but higher at the landscape shield level (41%).
Keywords: payments for ecosystem services; harmful effects of wind turbines; forest landscapes; landscape value trade; willingness to pay; willingness to accept; feasibility of a PES mechanism